Pengetahuan, sikap, kepercayaan, dan perilaku budaya tradisional pada generasi muda di Kota Bandung - Soepono, Sri Saadah; Hartati; Radiawan, Hari. (Jakarta : Departemen Pendidikan dan Kebudayaan, 1997)
Cultural attitudes of youths towards customs and traditions in Bandung, Jawa Barat Province.
Includes bibliographical references (p. 105-106).
Keywords: Youth -- Indonesia -- Bandung -- Attitudes; Public opinion -- Indonesia -- Bandung; Bandung (Indonesia) -- Social life and customs -- Public opinion